Measurements and analysis of the thermal properties of a sedimentary succession in Yangtze plate in China. (March 2020) - Luo, Jin; Qiao, Yu; Xiang, Wei; Rohn, Joachim
Abstract: A geological stratum is a rock or soil layer that has internally consistent characteristics and is distinguishable from adjacent layers. A stratigraphic section contains reference information for the strata of an associated sedimentary area. In this paper, the thermal properties of 36 rock formations in a succession of the Yangtze plate in China are studied. Thermal properties are analyzed with an emphasis on rock formations, rock lithological types and dry/saturated conditions. The results show that thermal conductivity varies dramatically with different rock lithological types, which range from 0.72 W m −1  K −1 to 4.49 W m −1  K −1 . The analysis of biochemical sedimentary rocks shows that silicate has the highest thermal conductivity, followed by dolomite and limestone; this variation is due to the differences in rock-forming minerals. The thermal conductivity of the clastic rocks is mainly determined by the type of minerals, the porosity and the water content. Compared to dry samples, the thermal conductivity and volumetric heat capacity of saturated samples are higher. Moreover, the thermal conductivity data of nine other locations in the Yangtze plate are compared with the stratigraphic data. This analysis shows that thermal conductivity matches very well for most of the geological formations, with the exception of sandstone, which exhibits a significant deviation across formations. Finally, the thermal properties for the Yangtze plate are mapped for insight on their spatial distribution. Highlights: Thermal properties of 36 rock formations in a sedimentary succession are measured. Thermal conductivity varies dramatically with lithological types of rocks. Two categories rocks are studied with emphasis on sedimentogenesis. Thermal properties of Yangtze plate are mapped for insights on spatial distribution.